Blood, sweat, and my rock 'n' roll years : is Steve Katz a rock star? - Katz, Steve, 1945- (Lyons Press, 2015)
By a founding member of the legendary Blues Project and Blood, Sweat & Tears-a man who played the Monterey Pop Festival and Woodstock, had affairs with famous female folk singers, and jammed with everyone from Mose Allison to Jimi Hendrix-comes a blues-folk-rock memoir of resigned existentialism and decidedly New York Jewish humor (what if Woody Allen had been a rock star?).